Moment theory for kinetic study of chromatography - Miyabe, Kanji (TrAC, Trends in analytical chemistry (Regular ed.), 2016)
•A framework of moment theory for the kinetic study of chromatography is introduced.•Moment equations for the analysis of mass transfer and reaction kinetics are indicated.•Recent progress of research subjects relating to the moment theory is explained. It is required to study the mass transfer and reaction kinetics for well understanding some important characteristics and mechanisms of chromatography. A great number of studies have been pursued so far on the retention equilibrium in chromatography. On the contrary, some intrinsic difficulties prevent the progress of the kinetic study. Moment theory is one of effective strategies for analyzing chromatographic behavior from the kinetic point of view. In this review, at first, a framework of the moment analysis theory is explained. Then, the recent progress of some related research subjects is introduced.